Synthesis of New 5- or 7-Substituted 3-Nitroimidazo[1,2-a]pyridine Derivatives Using SNAr and Palladium-Catalyzed Reactions To Explore Antiparasitic Structure–Activity Relationships - Paoli-Lombardo, Romain; Primas, Nicolas; Bourgeade-Delmas, Sandra; Sournia-Saquet, Alix; Castera-Ducros, Caroline; Jacquet, Inès; Verhaeghe, Pierre; Rathelot, Pascal; Vanelle, Patrice (Synthesis, 2024)
To study the antikinetoplastid structure–activity relationships in a 3-nitroimidazo[1,2-a]pyridine series, we explored the substitution of positions 5 and 7 of the scaffold, developing nucleophilic aromatic substitution reactions and palladium-catalyzed Suzuki–Miyaura, Sonogashira, and Buchwald–Hartwig cross-coupling reactions that had never been reported at these positions in this series. In four steps from 2-amino(bromo)pyridines, 33 original compounds were obtained, allowing a better definition of the antiparasitic pharmacophore.
Keywords: nitroaromatic compounds; imidazo[1,2-a]pyridines; kinetoplastids; nucleophilic aromatic substitution; palladium-catalyzed cross-coupling reactions; microwave irradiation